Peningkatan SDM Masyarakat Desa Dalam menggerakkan UMKM Desa Wajak: Sukolilo, Kecamatan Wajak, Kabupaten Malang, Provinsi Jawa Timur - Wiwit Setyo Wardani; Dita Rachmawati; Ferra Eka Ramadhani (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2023)
Human resources from Kelantan villages are frequently undervalued in terms of promoting MSMEs; HR is frequently viewed just as a production tool. This service aims to give training and help to MSME moms in Kelantan Village, West Brandan District. Human resource competences include issues like legal compliance, job quality and salary determination, and product performance evaluation. Another goal of this service is to give counseling and training in creative economy and community-based HR management abilities. The creative economy is a key component of Indonesia's future economy. This is consistent with the Ministry of Tourism and Creative Economy's program for Indonesia's "17 Creative Economy Subsectors."The target audience consists of MSMEs in Sukolilo Village, Wajak District, Malang Regency. This service activity is implemented through the delivery of materials, lectures, questions and answers, and conversations.